Hashemite Kingdom of Jordan : Understanding How Gender Norms in MNA Impact Female Employment Outcomes - World Bank (World Bank, Washington, DC, 2018)
Do women in Jordan want to work? How do men feel about working women in their family? To what extent do personal beliefs and societal expectations influence a woman's decision to work and why should this matter in development interventions? The Jordanian government and development partners have invested heavily in promoting women's economic inclusion. However, Jordan has the lowest female labor force participation (FLFP) in the world of a country not at war. As development practitioners working on issues related to social and economic inclusion in the Middle East and North Africa (MNA) region, we ask ourselves these questions to help us understand binding constraints that prevent excluded groups, such as women and youth, from having equal opportunity to improve their quality of life. We also ask these questions to distinguish between our own and others' perceived notion of inclusiveness. Building evidence from the field is key to enable development practitioners design more effective interventions to support female labor force participation.